Rethinking Engineering in Social Projects: Contributions from anthropology based on the experience of “Ingeniería Sin Fronteras – Argentina” (2022)
In the contemporary world, several social and development projects demand the participation of engineering professionals.Although, universities do not usually train technical professionals with an integral profile to work in interdisciplinary teamswith perspectives that benefit the understanding of complex social problems. In this article, we seek to question the representations and practices of engineering from the contributions of social anthropology and the gender perspective based on the work experience at “Ingeniería Sin fronteras- Argentina”. We understand that in social projects somedisciplinary paradigms such as verticality, coloniality and the supposed technological neutrality are put in tension. In thisway, we look forward to contributing to the debate on the role of engineering in society and the question of finding other ways to design and implement technological solutions in contexts of high social vulnerability.